That was then, this is now - Hinton, Susan Eloise (Puffin Books, 1998)
Sixteen-year-old Mark and Bryon have been like brothers since childhood, but now, as their involvement with girls, gangs, and drugs increases, their relationship seems to gradually disintegrate.